Política de vivienda y movilidad residencial en la Ciudad de México - Isunza Vizuet, Georgina (El Colegio de México A.C., 2010)
This study examines the differential impact of the expansion of mortgage lending on residential mobility patterns in the metropolitan area of Mexico City. The increasing involvement of business real estate housing supply through the construction of large housing estates primarily located in peripheral municipalities. This has favored the dominance of population flows between peripheral areas on the traditional patterns of mobility center-periphery, and a process of residential mobility, resulting in fragmented and scattered residential clusters as they move away from central areas of the city.